The WW1 Domain Enhances Autoinhibition in Smurf Ubiquitin Ligases. Issue 24 (6th December 2019) - Ruetalo, Natalia; Anders, Samira; Stollmaier, Carsten; Jäckl, Magnus; Schütz-Stoffregen, Mira C.; Stefan, Nadine; Wolf, Christine; Wiesner, Silke
Abstract: Downregulation of ubiquitin (Ub) ligase activity prevents premature ubiquitination and is critical for cellular homeostasis. Nedd4 Ub ligases share a common domain architecture and yet are regulated in distinct ways through interactions of the catalytic HECT domain with the N-terminal C2 domain or the central WW domain region. Smurf1 and Smurf2 are two highly related Nedd4 ligases with ~70% overall sequence identity. Here, we show that the Smurf1 C2 domain interacts with the HECT domain and inhibits ligase activity in trans . However, in contrast to Smurf2, we find that full-length Smurf1 is a highly active Ub ligase, and we can attribute this striking difference in regulation to the lack of one WW domain (WW1) in Smurf1. Using NMR spectroscopy and biochemical assays, we identified the WW1 region as an additional inhibitory element in Smurf2 that cooperates with the C2 domain to enhance HECT domain binding and Smurf2 inhibition. Our work provides important insights into Smurf regulation and highlights that the activities of highly related proteins can be controlled in distinct ways. Graphical abstract: Image 1 Highlights: We studied the regulation of the highly related ubiquitin ligases Smurf1 and Smurf2. The lack of a WW1 domain renders Smurf1 constitutively active. In Smurf2, the WW1 domain forms a supramodule with the C2 domain. The C2-WW1 supramodule enhances HECT domain binding and Smurf2 inhibition. Our results show that closely related proteins can be controlled in distinct ways.